Advantages and barriers of using telemedicine in the follow-up of patients with heart failure (Research, Society and Development, 2021)
Telemedicine is the remote delivery of health care services in situations that distance is a critical factor. Amidst of the COVID 19 scenario, telemedicine has undergone many advances, however, there are still obstacles in its applicability. In this context, the present study aims to conduct a systematic review focusing on the advantages and barriers of using telemedicine in monitoring patients with heart failure (HF). For this purpose, a bibliographic survey was carried out through the electronic library PubMed, having as inclusion criteria articles whose central theme was the use of telemedicine in monitoring patients with HF published between 2017 and 2021. In total, 95 articles were identified, of which only 13 had relevant contributions to the present study. Analyzing them, it was identified that the use of remote health services provides an increase in patient adherence to treatment, thus reducing the rate of hospitalization and death, in addition it has excellent cost-benefit. However, the impossibility of carrying out the physical examination and the population's lack of access to electronic devices and internet are obstacles that hinder its applicability. Therefore, despite the many benefits provided by telemedicine for patients with HF, well-established logistics are necessary for these barriers to be overcome.